2008
DOI: 10.1097/wad.0b013e31816c92bf
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Alzheimer Pathology in Late-Life Depression With PET and Pittsburgh Compound-B

Abstract: There is increasing evidence for an empiric link between late-life depression and Alzheimer disease (AD). The neuropathology of AD, previously only confirmed at autopsy, may now be detectable in vivo using selective imaging ligands for β-amyloid. Positron emission tomography (PET) with [ 11 C] 6-OH-BTA-1 [Pittsburgh Compound-B (PiB)] has shown high tracer retention in cortical areas in patients with clinical diagnoses of probable AD and low retention in age-matched controls. We also previously reported variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 57 publications
10
92
2
Order By: Relevance
“…In addition, our high-resolution structural brain networks showed sporadic prefrontal regions that were associated with a discrepant nodal efficiency in the WM networks in the RGD compared with aMCI patients. The prefrontal lobe system usually plays a vital role in mood regulation and cognitive function (Milak et al, 2005;Bae et al, 2006), which is involved in the pathogenesis of RGD and aMCI (Butters et al, 2008). The finding further suggests that regional characteristics of the prefrontal regions may also be a valuable marker for distinguishing RGD from aMCI.…”
Section: Common Deficits Of Regional/ Connection Characteristics In Tmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, our high-resolution structural brain networks showed sporadic prefrontal regions that were associated with a discrepant nodal efficiency in the WM networks in the RGD compared with aMCI patients. The prefrontal lobe system usually plays a vital role in mood regulation and cognitive function (Milak et al, 2005;Bae et al, 2006), which is involved in the pathogenesis of RGD and aMCI (Butters et al, 2008). The finding further suggests that regional characteristics of the prefrontal regions may also be a valuable marker for distinguishing RGD from aMCI.…”
Section: Common Deficits Of Regional/ Connection Characteristics In Tmentioning
confidence: 72%
“…Specifically, approximately one-half of demonstrated brain ␤-amyloid accumulation in the aforementioned cortical areas among RGD is in a pattern characteristic of early AD (Butters et al, 2008). Such a changing pattern was also observed in amnestic mild cognitive impairment (aMCI) pathologic (Jagust et al, 2010) and neuroimaging (Pihlajamäki et al, 2009) studies.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…While clinical depression was not assessed this study, the finding of Ab-status differences on the level of mean depressive symptom count is notable in light of growing evidence for an association between history of depression and risk for AD, 30 and between latelife depression and presence of AD-like Ab deposition. 31 We have shown that Ab deposition among oldest-old dementia-free survivors is associated with greater longitudinal cognitive decline. AD-like Ab deposition, measurable in about half of the population without dementia in the 9th and 10th decades of life, has demonstrable, if subtle, cognitive and behavioral correlates.…”
Section: Resultsmentioning
confidence: 99%
“…In a small study of persons without dementia, depression was associated with elevated cortical uptake of Pittsburgh Compound B, suggesting elevated ␤-amyloid. 32 In persons with AD, a history of depression has been associated with relatively higher levels of AD pathologic lesions. 33,34 However, in 2 large clinical-pathologic studies of persons with and without dementia, level of depressive symptoms in the last years of life was not related to the pathologic hallmarks of AD or other common dementias.…”
Section: Discussionmentioning
confidence: 99%